Neurovascular complications of antiphospholipid syndrome: a narrative review - Mendes, George Nilton Nunes; Morais, Alessandra Braga Cruz Guedes de; Gioia, Laura Catherine; Jacquin, Grégory; Poppe, Alexandre Y.; Soga, Felipe Hideki; Andrade, João Brainer Clares de (Arquivos de Neuro-Psiquiatria, 2024)
Background Antiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by thrombosis, pregnancy complications, and other nonthrombotic manifestations in the presence of antiphospholipid antibodies. Neurovascular complications, including ischemic stroke, cerebral venous thrombosis and cognitive impairment, pose significant challenges in management.Objective To comprehensively review relevant and updated clinical aspects of neurovascular manifestations of APS.Methods We conducted a narrative review using the PubMed, EMBASE, and Cochrane Library databases with medical terms related to APS and its neurovascular manifestations. English-language studies, published between January 1, 2015, and March 2024, were included. Key publications outside this timeframe were also considered. Studies with higher levels of evidence, such as randomized controlled trials and meta-analyses, were prioritized for inclusion.Results Stroke is a prevalent complication in APS, with arterial thrombosis being a predominant mechanism. Despite recent trials, direct oral anticoagulants (DOACs) have not shown superiority over vitamin K antagonists (VKAs) for secondary prevention in this population. Cerebral venous thrombosis (CVT), although rare, can also occur in APS, and while DOACs have shown promise as a treatment in a general population, caution is warranted due to potential harm. Cognitive impairment affects a considerable proportion of APS patients, with thrombotic and nonthrombotic mechanisms contributing to its pathophysiology. Future research should focus on optimal management strategies for cognitive impairment and the efficacy of anticoagulation and immunosuppression.Conclusion Understanding the complex interplay of neurovascular manifestations in APS is essential for guiding clinical decisions and improving patient outcomes. Despite advancements, some challenges remain in establishing effective preventive and treatment measures, highlighting the need for further research in this field.
Keywords: Antiphospholipid Syndrome; Stroke; Cognition; Venous Thrombosis; Complications